PLK3 weakens antioxidant defense and inhibits proliferation of porcine Leydig cells under oxidative stress - Chujie Chen; Jinyan He; Weixian Huang; Dong Xu; Zhaohui Li; Anqi Yang (Scientific Reports)
Abstract Aging is characterized by cellular degeneration and impaired physiological functions, leading to a decline in male sexual desire and reproductive capacity. Oxidative stress (OS) lead to testicular aging by impairing the male reproductive system, but the potential mechanisms remain unclear. In the present study, the functional status of testicular tissues from young and aged boars was compared, and the transcriptional responses of Leydig cells (LCs) to hydrogen peroxide (H2O2)-induced senescence were explored, revealing the role of OS in promoting aging of the male reproductive system. 601 differentially expressed genes (DEGs) associated with OS, cell cycle regulation, and intracellular processes were identified. These DEGs were significantly enriched in critical aging pathways, including the p53 signaling pathway, autophagy, and cellular senescence. Protein-protein interaction (PPI) network analysis unveiled 15 key genes related to cell cycle and DNA replication, with polo-like kinase 3 (PLK3) exhibiting increased expression under OS. In vitro, PLK3 knockdown significantly enhanced the viability and antioxidant capacity of LCs under OS. This study deepens our understanding of how LCs respond to OS and provides new therapeutic targets for enhancing cellular resistance to oxidative damage and promoting tissue health.